Amniotic fluid levels of phospholipase A2 in fetal rats with retinoic acid induced myelomeningocele: the potential "second hit" in neurologic damage. (16th September 2016) - Agarwal, R.; Thornton, M. E.; Fonteh, A. N.; Harrington, M. G.; Chmait, R. H.; Grubbs, B. H.
Abstract: Objectives : There is growing evidence of ongoing, in utero neurological damage in fetuses with myelomeningocele (MMC). Phospholipase A2 (PLA2 ) has known neurotoxic properties and is predominantly present in its secretory isoform (sPLA2 ) in meconium, the passage of which is increased in MMC fetuses. The objective of this study was to determine if amniotic fluid (AF) levels of PLA2 are elevated in a rat model of MMC. Methods : Timed pregnant Sprague–Dawley rats were gavage fed 60 mg/kg/bodyweight retinoic acid (RA) in olive oil at embryonic day 10 (E10). Amniocentesis was performed at multiple gestational time points on MMC fetuses, RA-exposed fetuses without MMC and control fetuses. AF PLA2 levels were analyzed by a fluorescent enzyme activity assay. PLA2 isoforms were determined by measuring activity in the presence of specific inhibitors. Results : There was no difference in AF PLA2 activity between groups on E15. PLA2 activity was significantly increased in MMC fetuses on E17, E19 and E21 ( p < 0.001). Secretory PLA2 primarily accounted for the overall greater activity. Conclusions : PLA2 levels are elevated in the AF of fetal rats with MMC and may contribute to ongoing neural injury. This pathway may be a useful drug target to limit ongoing damage and better preserve neurologic function.